2022
DOI: 10.5935/0004-2749.20230041
|View full text |Cite
|
Sign up to set email alerts
|

Eye-related emergency visits during the early phase of the coronavirus disease pandemic in a reference hospital in Sao Paulo, Brazil

Abstract: To evaluate the profile of emergency eye-related visits at a reference eye hospital in Sao Paulo during the first months of the quarantine due to the coronavirus disease (COVID-19) pandemic and to compare it with that in the same period of the previous year. Methods: Data were obtained from the emergency department of Ophthal Hospital Especializado, Sao Paulo, Brazil. All the cases registered between March 23 and May 19, 2020, were included in the study as Group 2020. The cases registered between March 23 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…General emergency visits were reported to have decreased up to 72.5% in India, while ocular emergency consultations were reported to have decreased up to 53.1% in the United Kingdom, very close to the results found in our study. (12)(13)(14) Another study performed in a private service in São Paulo has shown a decrease of 46.2%, (15) slightly lower than our results from a public service.…”
Section: Resultscontrasting
confidence: 79%
“…General emergency visits were reported to have decreased up to 72.5% in India, while ocular emergency consultations were reported to have decreased up to 53.1% in the United Kingdom, very close to the results found in our study. (12)(13)(14) Another study performed in a private service in São Paulo has shown a decrease of 46.2%, (15) slightly lower than our results from a public service.…”
Section: Resultscontrasting
confidence: 79%